Answer:
See attachment
Step-by-step explanation:
The given equation is 3x-4y=12
Let us solve for y to get:
[tex]4y=3x-12[/tex]
[tex]y=\frac{3}{4}x-\frac{12}{4}[/tex]
[tex]y=\frac{3}{4}x-3[/tex]
When x=0, we get:
[tex]y=\frac{3}{4}*0-3=-3[/tex]...(0,-3)
When x=4, we get
[tex]y=\frac{3}{4}*4-3=0[/tex]...(4,0)
When x=8, we get;
[tex]y=\frac{3}{4}*8-3=3[/tex]...(8,3)
When x=12, we get;
[tex]y=\frac{3}{4}*12-3=6[/tex]...(12,6)
These points are plotted and they all lie on this line.
When substitute all these points back into the equation they must satisfy.
3*4-4*0=12
3*0-4*-3=12
3*8-4*3=12
3*12-4*6=12
The table is shown in the attachment